Perlindungan Hukum Terhadap Anak Korban Penelantaran Orang Tua di Kota Mataram dalam Perspektif Hukum Hindu dan Undang-Undang Nomor 35 Tahun 2014 Tentang Perlindungan Anak - Krisnadhi Winangun; I Gusti Ayu Agung Andriani; Ni Nyoman Ernita Ratnadewi; I Nyoman Suarna; I Gusti Ayu Aditi; Habibi Habibi (Lembaga Pengembangan Kinerja Dosen, 2025)
The purpose of this research is to understand the legal protection for children who are victims of parental neglect and to identify the forms of accountability for parents who neglect their children. The type of research used in this study is normative-empirical research. The data in this research were obtained through observation, interviews, documentation, and literature studies using the legislative approach, conceptual approach, and case approach. The discussion in this research refers to the Law of the Republic of Indonesia Number 35 Year 2014 concerning child protection, which states that legal protection for children can be interpreted as efforts to legally protect various freedoms and fundamental rights of children. In Hinduism, it is also explained that protection for children must be carried out since the child is in the womb. It is not acceptable for a child in the womb to receive any mistreatment from anyone, especially after the child is born into the world and lives like other humans in general.